Pengaruh Struktur Aset dan Biaya Keagenan Terhadap Kebijakan Hutang Dimediasi dengan Profitabilitas - Hermanto; Liem, Dravinca Rona (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
The purpose of this study is to determine the determinants of debt policy (leverage) such as asset structure and agency costs and profitability as intervening variables. This study utilizes multiple linear analysis methods with secondary data types. The results of the study show that asset structure and agency costs simultaneously affect profitability, and asset structure, agency costs and profitability also simultaneously affect leverage. Asset structure has a negative impact on profitability and has a positive impact on leverage. Agency costs affect profitability negatively and affect leverage positively. Profitability has a negative effect on leverage. The research findings show that companies that pay attention to asset structure and agency costs can overcome debt policies and increase their profitability. Keywords: Asset, Agency Cost, Profitability, Leverage